Difficult airway and difficult intubation in postintubation tracheal stenosis: a case report and literature review - Zarogoulidis P; Kontakiotis T; Tsakiridis K; Karanikas M; Simoglou C; Porpodis K; Mitrakas A; Esebidis A; Konoglou M; Katsikogiannis N; Zervas V; Aggelopoulou C; et al. (Therapeutics and Clinical Risk Management, 2012)
Paul Zarogoulidis,1 Theodoros Kontakiotis,1 Kosmas Tsakiridis,2 Michael Karanikas,3 Christos Simoglou,4 Konstantinos Porpodis,1 Alexandros Mitrakas,3 Agisilaos Esebidis, 3 Maria Konoglou,5 Nikolaos Katsikogiannis,6 Vasilis Zervas,1 Christina Aggelopoulou,7 Dimitrios Mikroulis,4 Konstantinos Zarogoulidis11Pulmonary Department, "G Papanikolaou" General Hospital, Aristotle University of Thessaloniki, Thessaloniki, Greece; 2Cardiothoracic Department, Saint Luke Private Hospital, Thessaloniki, Greece; 31st University Surgery Department, 4Cardiothoracic Department, University General Hospital of Alexandroupolis, Democritus University of Thrace, Alexandroupolis, Greece; 51st Pulmonary Department, "G Papanikolaou" General Hospital, Aristotle University of Thessaloniki, Thessaloniki, Greece; 6Surgery Department (NHS), 7Neurology Department (NHS), University General Hospital of Alexandroupolis, Democritus University of Thrace, Alexandroupolis, GreeceAbstract: Management of a "difficult airway" remains one of the most relevant and challenging tasks for anesthesiologists and pulmonary physicians. Several conditions, such as inflammation, trauma, tumor, and immunologic and metabolic diseases, are considered responsible for the difficult intubation of a critically ill patient. In this case report we present the case of a 46-year-old male with postintubation tracheal stenosis. We will focus on the method of intubation used, since the patient had a "difficult airway" and had to be intubated immediately because he was in a life-threatening situation. Although technology is of utter importance, clinical examination and history-taking remain invaluable for the appropriate evaluation of the critically ill patient in everyday medical life. Every physician who will be required to perform intubation has to be familiar with the evaluation of the difficult airway and, in the event of the unanticipated difficult airway, to be able to use a wide variety of tools and techniques to avoid complications and fatality.Keywords: difficult airway, bronchoscopic intubation, predictive factors, predictive scales